2009
DOI: 10.1007/s10853-009-4144-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallographic orientation on the early stages of oxidation in nickel and chromium

Abstract: Surface orientation plays an important role in the oxidation behavior of single crystals where studies have found the relative oxidation rates for surfaces with different orientations. However, most materials are polycrystalline and contain myriad orientations that contribute to the overall oxidation process. Here we determine the effects of orientation on the early stages of oxidation behavior as a function of surface orientation for polycrystalline nickel (face-centered cubic) and chromium (body-centered cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 28 publications
(76 reference statements)
4
7
0
1
Order By: Relevance
“…Thus, E values change significantly with interfacial configuration, with the field strength across the Ni(111)/NiO interface substantially lower than that for the other two interfaces. Although in the absence of knowing the complete electrostatic potential drop across the oxide itself we cannot predict oxide growth rates for the various interfaces, the calculations do suggest that the electrostatic driving force for electron transfer into the NiO from the Ni metal is weakest at the Ni(111)/NiO interface, a picture generally consistent with experimental observations showing Ni metal surfaces are highly protective along the ⟨111⟩ direction and less protective along the ⟨100⟩ direction …”
Section: Resultssupporting
confidence: 62%
“…Thus, E values change significantly with interfacial configuration, with the field strength across the Ni(111)/NiO interface substantially lower than that for the other two interfaces. Although in the absence of knowing the complete electrostatic potential drop across the oxide itself we cannot predict oxide growth rates for the various interfaces, the calculations do suggest that the electrostatic driving force for electron transfer into the NiO from the Ni metal is weakest at the Ni(111)/NiO interface, a picture generally consistent with experimental observations showing Ni metal surfaces are highly protective along the ⟨111⟩ direction and less protective along the ⟨100⟩ direction …”
Section: Resultssupporting
confidence: 62%
“…Similar results as in present work were also reported by other researchers [41]. After investigation of the initial oxidation of polycrystalline Ni and Cr, it was reported that oxidation rate in Ni changes with crystal orientation in following order (111) b (110) b (100) while for polycrystalline Cr changes with crystal orientation as (111) N (110) N (100) [41]. Orme et al also investigated the anisotropic corrosion behavior of Inconel 600 [36] and alloy 22 [42] in HCl solution.…”
Section: Correlate Grain Orientation With Relative Oxide Thicknesssupporting
confidence: 93%
“…Here, although the oxidation velocity may still relate with the atomic density of different planes like near (111) grains always obtain higher resistance than other grains, it may also relate with the oxide surface morphology formed on grains. Similar results as in present work were also reported by other researchers [41]. After investigation of the initial oxidation of polycrystalline Ni and Cr, it was reported that oxidation rate in Ni changes with crystal orientation in following order (111) b (110) b (100) while for polycrystalline Cr changes with crystal orientation as (111) N (110) N (100) [41].…”
Section: Correlate Grain Orientation With Relative Oxide Thicknesssupporting
confidence: 91%
“…It was also reported that grain boundaries influence the formation of a protective alumina layer. In addition to the existence of grain boundaries, grain orientation is known to affect the oxide formation of pure metals and alloys …”
Section: Introductionmentioning
confidence: 99%